Actual Incidence and Clinical Behaviour of Follicular Thyroid Carcinoma: An Institutional Experience - Carmela De Crea; Marco Raffaelli; Luca Sessa; Simona Ronti; Guido Fadda; Chiara Bellantone; Celestino Pio Lombardi (The Scientific World Journal)
Follicular thyroid carcinoma classically accounts for 10–32% of thyroid malignancies. We determined the incidence and the behaviour of follicular thyroid carcinoma in an endemic goitre area. A comparative analysis between minimally invasive and widely invasive follicular thyroid carcinoma was performed. The medical records of all patients who underwent thyroidectomy from October 1998 to April 2012 for thyroid malignancies were reviewed. Those who had a histological diagnosis of follicular carcinoma were included. Among 5203 patients, 130 (2.5%) were included. Distant metastases at presentation were observed in four patients. Sixty-six patients had a minimally invasive follicular carcinoma and 64 a widely invasive follicular carcinoma. In 63 patients an oxyphilic variant was registered. Minimally/widely invasive ratio was 41/26 for usual follicular carcinoma and 25/38 for oxyphilic variant (P<0.05). Patients with widely invasive tumors had larger tumors (P<0.001) and more frequently oxyphilic variant (P<0.05) than those with minimally invasive tumours. No significant difference was found between widely invasive and minimally invasive tumors and between usual follicular carcinoma and oxyphilic variant regarding the recurrence rate (P=NS). The incidence of follicular thyroid carcinoma is much lower than classically retained. Aggressive treatment, including total thyroidectomy and radioiodine ablation, should be proposed to all patients.